1997
DOI: 10.3354/meps152301
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of a bacterivorous ciliate by the oyster Crassostrea gigas:protozoa as a trophic link between picoplankton and benthic suspension-feeders

Abstract: The linked concepts of 'microbial loop' and 'protozoan trophic link' have been very well documented in filter-feeding microzooplankton such as copepods, but have not been applied to energy transfer to benthic suspensionfeedlng macrofauna, with the exception of the recent demonstration of heterotrophlc flagellate assimilation by mussels. The oyster Crassostrea gigas o b t a~n s energy resources by filtering microalgae (-5 to 100 pm). However, in turbld estuaries, lighl-limited phvtoplanktonic production cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 22 publications
5
46
0
Order By: Relevance
“…Pelagic secondary producers (protozoa and zooplankton): Heterotrophic protozoa are a trophic intermediary between bacteria and oysters but have not been studied quantitatively in MOB (Le Gall et al 1997, Dupuy et al 1999, 2000. Thus, concentration data measured in the English Channel (Newell & Linley 1984) are used instead.…”
Section: Methodsmentioning
confidence: 99%
“…Pelagic secondary producers (protozoa and zooplankton): Heterotrophic protozoa are a trophic intermediary between bacteria and oysters but have not been studied quantitatively in MOB (Le Gall et al 1997, Dupuy et al 1999, 2000. Thus, concentration data measured in the English Channel (Newell & Linley 1984) are used instead.…”
Section: Methodsmentioning
confidence: 99%
“…This low retention is attributed to the absence of eulatero-frontal cirri on the gill filaments. However the indirect ingestion of the picoplanktonic biomass can be mediated by heterotrophic protists which then represent a trophic link between cyanobacteria and suspension-feeders (Le Gall et al 1997, Dupuy et al 1999.…”
Section: Stationmentioning
confidence: 99%
“…Recently, Bardouil et al (1996) showed that Crassostrea gigas easily consumes a nontoxic dinoflagellate and Kreeger & Newel1 (1996) clearly demonstrated in mussels the ingestion and assimilation of bacterial carbon via heterotrophic flagellates. From experimental work, Le Gall et al (1997) reported significant retention and ingestion of cultured bacterivorous ciliates, Uronema sp., by the oyster C. gigas. Heterotrophic protists, which are abundant in coastal ecosystems, may thus constitute an alternative or complementary food resource for benthic filter feeders, allowing the indirect recuperation of DOM and picoplanktonic production otherwise not accessible to them.…”
Section: Introductionmentioning
confidence: 99%